Laboratory parameters in differential diagnosis of iron deficiency anemia and chronic infections anemia among children - Medovic, Rasa; Igrutinovic, Zoran; Jancic, Aleksandra; Vujic, Ana (Medicinski časopis, 2012)
Introduction: Sideropenic anemia, caused by lack of iron, is the most common anemia in children age, and the second one is anemia that appears as a consequence of some chronic infection and is called secondary anemia. Same laboratory tests are used for diagnosis of these types of anemia. Aims of the study: To establishing the valid laboratory parameters which can be used in differential diagnosis of sideropenic and secondary anemia among children. Sources and methods: In infirmary of hematology on Pediatric clinic KC Kragujevac, from 1st December 2010. to 31st January 2011., 35 children with sideropenic anemia, 35 children with anemia, caused by chronic infections and 35 healthy children were involved in the research. To all children it has been done: number of leukocytes (Le), number of eryithrocytes (Er), number of platelets (Tr), hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red blood cell distribution width (RDW), serum iron (Fe), total iron binding capacity (TIBC), unsaturated iron binding capacity (UIBC) and feritin. Statistical processing of the data contained middle, the lowest and the highest valuation, and statistical importance. Results: The number of Le are increased in the group with secondary anemia compared to the control group and the group with sideropenic anemia. The number of Er shows no difference within the groups of studied children. There is no difference in the values of Hb, Hct, MCHC, number of Tr and serum Fe between the groups with different types of anemia, but there is a difference between the groups with anemia compared to the control group. The values of MCV and MCH show the difference between the groups, with the highest mean value in the control group, and the loweest mean value in the group of children with sideropenic anemia. The values of RDW, TIBC and UIBC are increased in the group with sideropenic anemia, compared to the control group and the group with secondary anemia. The values of feritin are different between the groups, with the highest mean value in the group with secondary anemia and the lowest mean value in the group with sideropenic anemia. Conclusion: Valid laboratory parameters in differential diagnosis of sideropenic and secondary anemia are number of Le, MCV, MCH, RDW, TIBC, UIBC and feritin. Key words: Sideropenic anemia, chronic infections anemia, laboratory tests, children